Pengaruh suplementasi zink (Zn) terhadap diare pada penderita umur 6-36 bulan yang dirawat di RSUD Dr. Soedarso Pontianak, Kalimantan Barat - Jurianto Gambir; Madarina Julia; Muhammad Jufrrie (Jurnal Gizi Klinik Indonesia, 2005)
Background: Diarrhoea is one of the major causes of infants and childhood death in Indonesia. Malnutrition and zinc deficiency in diarrhoea may lead to impaired immunity.Objective: To assess the influence of zinc supplementation on the duration of diarrhoea and the frequency of watery stools in under-three-year-old childrenMethod: This was a double-blind randomized controlled clinical trial, with 31 children in the supplemented group and 33 children in the placebo group. All children had acute watery diarrhea and were given supplementation within 24 hours of admission. Daily supplementation of 20 mg zinc was given to the experimental group.Results: The supplemented group had a shorter hospitalization compared to the placebo. Beginning from the second day of supplementation, the frequency of watery stools in the supplemented group was significantly less than in the placebo group (p<0.001). While there was a significant decrease in the concentration of zinc in the serum of the placebo group, there was a slight increase in the supplemented group.Conclusion: Zinc supplementation can shorten hospitalization and reduce the frequency of watery stools in children with diarrhoea.